Analisis Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen Pada Depot Aidrat Sunan Drajat Paciran Lamongan - Edy Anas Ahmadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research was conducted to see and determine the effect of service quality on customer satisfaction at refill drinking water depots in Aidrat (Air Asli Sunan Drajat) Lamongan, there are several factors that consumers can consider in assessing a service provided by the company, according to Zeithaml, Berry and Parasuraman (1985) quoted in Tjiptono (2000: 27-28) succeeded in identifying five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. Based on the results of the analysis that has been carried out on the effect of service quality (tangibles, reliability, responsiveness, assurance, and empathy) on consumer satisfaction at refill drinking water depots in Tirta Mulya, it can be concluded that based on the Multiple Regression Equation Analysis the result is Y = 2.047 + 0.441(X1)+ 0.113 (X2)+ 0.191 (X3) + 0.229 (X4) + 0.235 (X5). If the tangibles, reliability, responsiveness, assurance, and empathy variables are equal to zero, then the value of customer satisfaction is 2.047. If the quality of service changes by 1 then the tangibles variable will increase by 0.441%. Likewise for the reliability variable, which is equal to 0.113%. In contrast, the responsiveness, assurance, and empathy variables show positive parameters, namely 0.191%, 0.229%, and 0.235% respectively. This means that each addition of 1 variable will be followed by an increase in service quality. Based on the Coefficient of Determination Test (R2) the value of adjusted R is 0.961, this shows that 96.1% of customer satisfaction can be explained by the variables tangibles, reliability, responsiveness, assurance, and empathy. The remaining 3.9% is due to the influence of other variables not included in the model. Then based on the Simultaneous Test (F Test) Anova test it can be seen that the Fcount value is 461.654 > the Ftable value is 3.942, located in the rejection area so that Ho is rejected or Ha is accepted. It means that the tangibles, reliability, responsiveness, assurance, and empathy variables have a significant effect on the consumer satisfaction variable. And based on the Partial Test (t test) the results of testing the regression coefficient with tcount obtained the value of tcount tangibles of 4.473 (X1) > 1.661, reliability (X2) 2.053 > 1.661, responsiveness (X3) 3.083 > 1.661, assurance (X4) 4.718 > l1 .661, and empathy (X5) 5.325 > 1.661. Thus the variables tangibles, reliability, responsiveness, assurance, and empathy have a significant effect on consumer satisfaction variables.